Revolutionizing Drug Delivery: A Design Professional's Approach to Drug-loaded Transferosomal Vesicles for Transdermal Use - Subramaniyan, Gopinath; Shaik, Rubina; Ramana, Bachu Venkata; Meriton Stanley A; Srinivasan, Devasena (Pharmaceutical Nanotechnology, 2025)
<span class=
Keywords: Transdermal